'Gist watching can only take you so far': attitudes, strategies and changes in behaviour in watching films with captions. Issue 4 (8th August 2019) - Vanderplank, Robert
ABSTRACT: Watching foreign language programmes and films with captions (same-language subtitles intended for the deaf and hard-of-hearing) has been shown to assist learners in phonetic retuning, vocabulary acquisition and listening comprehension [e.g. Mitterer and McQueen, 2009. Foreign subtitles help but native-language subtitles harm foreign speech perception. PLOS ONE 4, no. 1: e7785. doi:10.1371/journal.pone.0007785 ; Montero Perez, Van Den Noortgate and Desmet, 2013. captioned video for L2 listening and vocabulary learning: A meta-analysis. System 41, no. 3: 720–739; Rodgers and Webb, 2017. The effects of captions on EFL learners' comprehension of English-language television programs. CALICO Journal 34, no. 1: 20–38]. However, relatively little is known about the outcomes and changes in viewing behaviour when learners watch with captions over an extended period if choice and control of viewing material are provided. This article reports qualitative findings of the EURECAP Project in which 36 learners of French, German, Italian and Spanish at intermediate level and above in a large UK university chose from a wide range of films on DVD with optional captions and watched them under their control in their own time. Their experiences as noted in viewing diaries revealed wide differences in viewing behaviour, attitudes to watching with captions and caption-guided viewing strategies over the period of the study. Participants fell into three broad strategic categories: Minimal users who were focused throughout on enjoying films as they would in their L1, evolving users who showed marked changes in their viewing behaviour over time, and maximal users who tended to be experienced at using films to enhance their language learning. We also compare participant behaviour with models of multimedia learning and suggest implications for future practice and research, especially in the light of global video streaming services with captions.